"It's all in the history": A service evaluation of the quality of radiological requests in acute imaging. Issue 3 (August 2018) - Davies, S.; George, A.; Macallister, A.; Barton, H.; Youssef, A.; Boyle, L.; Sequeiros, I.
Abstract: Introduction: The aim of this service evaluation project was to assess the quality of clinical details provided in radiological requests. Methods: A retrospective review of adult inpatient and emergency department radiological requests over a seven-day period was performed, using the local Clinical Radiological Information System (CRIS). Requests for plain film, CT, MRI and Ultrasound were assessed for the inclusion of a clinical question, lateralisation/localisation of signs or symptoms if required, and relevant past medical/surgical history if available. Results: 1548 imaging requests were analysed. 76% asked a specific clinical question. 74% of requests requiring localisation provided this. Of those cases with relevant past medical or surgical history available, 49% mentioned this. Emergency department (ED) requests provided localisation when required in 81% of cases compared to 62% of in-patients (p < 0.05). However, in-patient requests contained relevant past history in 53% of cases compared to 40% for ED requests (p = 0.00096). Compared to plain film requests, those for CT, MRI and Ultrasound studies were more complete in respect to inclusion of a clinical question (88% versus 72%, p < 0.05), localisation if required (83% versus 71%, p = 0.0007) and pertinent clinical history (67% versus 42%, p < 0.05). Requests from the weekend more often included a clinical question (83% vs 75%, p = 0.00054) and localisation if needed (84% vs 71%, p = 0.00188) compared with weekday requests. Conclusion: This large-scale service evaluation project shows that the quality of clinical details in requests for radiological investigations requires improvement, particularly in regard to inclusion of relevant past medical and surgical history. Highlights: 1548 imaging requests were analysed. 1187 (76%) of requests asked a specific clinical question. Of the 673 requests requiring localisation of signs, 499 (74%) included this. Of the 751 requests with available clinical history, 372 (49%) included this.